Fundamentals of PHP programming - Safari eBooks ([Place of publication not identified] : Stone River eLearning, 2014)
"Perfect for beginners and experienced PHP developers alike, the PHP Programming for Absolute Beginners course takes you from absolute beginner to understanding the basics of PHP in just a few hours. You will learn everything about the basics of PHP programming using real world examples. What Is PHP? PHP is an open source (free) scripting language that allows you to create dynamic websites and work with servers. PHP is now used on over 20 million websites and over 1 million servers worldwide."--Resource description page.
Title from resource description page (viewed October 23, 2015).
Keywords: PHP (Computer program language); Web sites -- Design; Web sites -- Programming; Electronic books